E-political caricatures-assisted cooperative learning: Disengaging EFL learners from individualistic, competitive and racial discrimination’s learning settings - Yohannes Telaumbanua; Yalmiadi Yalmiadi; Martini Martini; Hasbi Hasbi (Studies in English Language and Education, 2020)
This qualitative research was aimed at reviving the principles of cooperative learning in the English class and critically studying the effects of it on the learners’ learning process and language skills. A number of 25 English learners were purposively selected as research participants. Journal writing, observation, and interview were techniques for collecting the data. Miles and Huberman’s model was a way of analysing the data while triangulation (credibility and dependability) was the strategy for qualifying the finding. The findings indicated that the e-political caricatures-assisted cooperative learning requires authentic and global learning themes. It improves the qualities of the learners’ global awareness, intercultural competence, communication skills, collaboration (team building, capitalisation on one another resources, deep learning, mastering language knowledge or competence and skills of English), critical thinking skills, and creativity (4Cs). It then leads the learners to active learning, project and problem-based learning, and develops digital skills and digital literacy skills. When compared to the previous language skills, the levels of the learners’ English language performance were between “intermediate” (22 learners) and “proficient” (three learners). These results signify that cooperative learning strongly enhance the learners’ language competence and skills of English and inspire them to collaboratively work and learn regardless of differences. In conclusion, the cooperative learning treats equally all class members, understand and accept differences in race, level of language skills, intelligence, etc., to achieve the shared learning goals, and further encourage learners to construct the knowledge and skills of English collaboratively.